Implementasi Konsekuensi Logis dalam Menerapkan Kedisiplinan Peserta Didik di SMA Islam Parlaungan, Waru, Sidoarjo - Irfanurrasyid, Muhammad; Yuliastutik, Yuliastutik; Marfiyanto, Tri (Lembaga Yasin AlSys, 2025)
The low level of student discipline manifested in behaviors such as tardiness, disorderliness, and lack of academic responsibility remains a challenge in many schools, including SMA Islam Parlaungan Waru Sidoarjo. This study aims to examine the implementation of the logical consequences approach as an educational strategy for instilling discipline and building character. A qualitative case study method was employed, with data collected through interviews, observations, and documentation. The findings reveal that logical consequences were applied through reflective activities such as self-evaluation writing, recitation of Qur’anic verses, and discussions on accountability for one’s actions. This approach does not focus on punishment, but rather on cultivating an understanding of values and the impact of one’s behavior. As a result, students began to demonstrate increased awareness and positive behavioral change. The success of this strategy was supported by active teacher involvement, principal support, and parent collaboration. However, challenges persist, including uneven teacher comprehension of the logical consequences concept and the lengthy process required for value internalization. In conclusion, logical consequences offer an effective alternative disciplinary strategy by emphasizing a participatory approach and character formation. The findings imply the importance of developing a value- and logic-based disciplinary system to foster a positive and transformative learning environment.